2001
DOI: 10.1038/sj.gene.6363767
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in molecules of innate immunity and susceptibility to infection with Wuchereria bancrofti in South India

Abstract: A pilot study was conducted to determine if host genetic factors influence susceptibility and outcomes in human filariasis.Using the candidate gene approach, a well-characterized population in South India was studied using common polymorphisms in six genes (CHIT1, MPO, NRAMP, CYBA, NCF2, and MBL2) . A total of 216 individuals from South India were genotyped; 67 normal (N), 63 asymptomatic microfilaria positive (MF+), 50 with chronic lymphatic dysfunction/elephantiasis (CP), and 36 tropical pulmonary eosinophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
104
2
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 42 publications
6
104
2
2
Order By: Relevance
“…These results suggest that subjects bearing the mutant allele might exhibit an elevated susceptibility to infections sustained by parasites. This is in accordance with the findings reported by Choi et al, 15 who showed that in a total of 216 individuals from South India genotyped for Chit, the homozygous condition for the defective allele (the HH variant CHIT1 genotype) was associated with the absence of plasma Chit activity and with an elevated susceptibility to human Wuchereria bancrofti filarial infection, 15 confirming the importance of Chit in the protection against the chitin-containing pathogens. The higher levels of plasma Chit activity of African subjects might be surprising if we consider that these levels only reflect the homozygous wild-type allele condition, but the enlarged (up to 507 nmol/ml/h value) distribution curve of plasma Chit activity suggests that among the African population, several subjects may be affected by silent parasite infections, especially in the intestinal apparatus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results suggest that subjects bearing the mutant allele might exhibit an elevated susceptibility to infections sustained by parasites. This is in accordance with the findings reported by Choi et al, 15 who showed that in a total of 216 individuals from South India genotyped for Chit, the homozygous condition for the defective allele (the HH variant CHIT1 genotype) was associated with the absence of plasma Chit activity and with an elevated susceptibility to human Wuchereria bancrofti filarial infection, 15 confirming the importance of Chit in the protection against the chitin-containing pathogens. The higher levels of plasma Chit activity of African subjects might be surprising if we consider that these levels only reflect the homozygous wild-type allele condition, but the enlarged (up to 507 nmol/ml/h value) distribution curve of plasma Chit activity suggests that among the African population, several subjects may be affected by silent parasite infections, especially in the intestinal apparatus.…”
Section: Discussionsupporting
confidence: 91%
“…In our previous report, [9][10][11][12][13][14][15][16] a correlation between this parameter of macrophage activation, the level of serum ferritin and platelet count in children with acute malaria was found. This result suggested that Chit could have a role in the immune response and in the outcome of malaria infection.…”
Section: Discussionmentioning
confidence: 97%
“…This supports the existence of a 'healthy aging' phenotype in which individuals somehow delay or avoid major clinical disease and disability until late in life. Although previous studies have suggested that CHIT-1-deficient individuals show a certain degree of disadvantage, such as increased susceptibility to parasitic disease infections, to microorganisms containing chitin and to Gram-negative infections, 17,[31][32][33][34][35] other studies indicate that CHIT-1 deficiency is not a disadvantage but rather a selective advantage. [36][37] Given the very high gene frequency of the main mutant allele, as shown in this study, it seems more likely that in humans, selection has occurred in the direction of decreasing or eliminating the activity of this enzyme.…”
Section: Discussionmentioning
confidence: 94%
“…Increased ChT activity was also recorded in several other diseases, such as Niemann-Pick (Brinkman et al 2005), GM1 gangliosidosis , b-thalassemia (Barone et al 1999), sarcoidosis (Boot et al 2010), malaria (Barone et al 2003), atherosclerosis (Artieda et al 2003;Boot et al 1999), and fungal and bacterial infections (Iyer et al 2009;Labadaridis et al 1998). The role of ChT enzyme is unclear, but a possible role in defense against chitin-containing pathogens and host immune response has been suggested (Choi et al 2001;Di Luca et al 2007;Di Rosa et al 2005;Gordon-Thomson et al 2009;Malaguarnera et al 2005;van Eijk et al 2005).…”
Section: Discussionmentioning
confidence: 98%